Pengembangan bahan ajar berbasis muatan lokal pada mata kuliah Pendidikan Kewarganegaraan - Faisal, Emil El; Sulkipani, Sulkipani (Universitas Negeri Yogyakarta, 2016)
This research aimed at (1) developing teaching materials based on local content for Civic Education in University; and (2) describing the potential impact of local content on student consciousness on local culture. It was a developmental research. The subject were student registered in Civic Education Course (Mata Kuliah PKn) at History Department. Pilot project was validated through one to one, small group, and field evaluation. The analyzed result indicates that the developed instrument was valid and has potential impact. Supported data shows that the mean score prior to implementation was 6.86 and after implementation was 7.73. In other words, there was an increasing student achievement before and after its implementation. Accordingly, we suggest that this developed material could be implemented widely.